Historiografia biblijna w perspektywie hebrajskiej onomastyki: przypadek imion potomków Saula w Księgach Kronik (1Krn 8,33-34; 9,39-40) - Baraniak, Marek (Collectanea Theologica, 2020)
The names of Saul’s descendants appear in a different form in the books of Chronicles (1 Chr 8:33-34; 9:39-40) as compared to those in the books of Samuel (2 Sam 2-4; 9; 19; 21). In Chronicles the name Eshbaal is used instead of Ishbosheth, and Meribaal instead of Mephibosheth. This article describes the differences between these names in the context of early Hebrew epigraphy. The recalling of the original names of the first Judaean royal dynasty in the books of Chronicles could be explained not only with reference to the original version of the books of Samuel, but also from the oral tradition of Judea or from some documents of the royal archives that survived the Babylonian conquest.